The Mediating Effect of Consumer Brand Engagement on the Relationship between Social Media Marketing and Repurchase Intention - Asyhari, Asyhari; Ayuni, Sri; Primananda, Naufal Athiya; Saputri, Pungky Lela; Salleh, Wan Anisabanum (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
Social media become the primary marketing to enhance repurchase intention in e-commerce. However, not many companies in Indonesia use it to increase sales and gain profits. In addition, some literature reveals that the effect of social media marketing is not significant on repurchase intention. Several studies have shown that the dimensions of social media marketing have no significant effect on consumer behaviour. This study aimed to investigate the influence of social media marketing on repurchase intention through consumer brand engagement. The data were collected from 100 consumers of online Muslim fashion products in Central Java. Data were analysed using the model partial least square structural equation (PLS-SEM) with two steps namely confirmatory and structural analysis. The result indicated that social media marketing had a positive relationship with repurchase intention. Moreover, consumer brand engagement can be mediating the relationship between social media marketing and the repurchase intention of Muslim fashion products in Indonesia. The theoretical implication of this study is to provide an overview of the factors that shape consumer repurchase intention based on Stimulus-Organism-Response theory. The practical implication is that business practitioners should pay more attention to marketing through social media than conventional marketing.